Hubungan Antara Asupan Niasin Dan Asam Lemak Omega-3Denganstatus Depresi Pada Pasien Cedera Tulang Belakang Di RSO. Prof.Dr.R.Soeharso Surakarta - Cahya Ramadhani, Atika, Siti Zulaekah, A., M.Si, Setia Asyanti, S.Psi., M.Si., Psikolog (2015)
Introduction: spinal cord injury is a spinal cord damage in either the cervical vertebrae, toraka vertebrae, lumbar vertebrae, sacrum and coccygeu. Feelings of trauma to the symptoms of stress and depression experienced by people with spinal damage. Spinal cord injury with depression contribute to decreasing food intake. Objective: The aim of study was to determine the relationship between the intake of niacin and omega-3 fatty acid with status of depression in patients with spinal cord injuries in the RSO. Prof. DR. R. Soeharso Surakarta. Method: This was an observational study with cross sectional approach. The sample size of 35 people according to the inclusion criteria. Sampling by means of consecutive sampling. Adequate intake level data retrieval niacin and omega-3 fatty acids do form a 24-hour food recall for four days in the morning, afternoon and evening. Depression status data obtained by measuring the level of depression with a questionnaire Beck Depression Inventory (BDI). The statistical test used Spearman Rank. Results: The results showed 88.6% of the subjects had less niacin intake and 97.1% had intake of omega-3 fatty acid enough. Most subjects (31.4%) had mild depression levels. There is no relationship between intake of niacin with depression status (p = 0.276) and there was no association between intake of omega-3 fatty acids with depression status (p = 0.547). Conclusion: To sum up there is no association between the intake of niacin with depression status (p = 0.276) and there was no association between the intake of omega-3 fatty acids with depression status (p = 0.547). Keywords : Intake of Niacin, Omega-3 Fatty Acids and Depression Status Reference : 56 (1985 - 2013)